ENZOOHC ON A RABBIT STOCK - FARM CAUSED BY BORDETELLA BRONCHISEPTICA - ΒΟΓΙΑΖΑΣ Δ. (Journal of the Hellenic Veterinary Medical Society, 1972)
On a rabbit stock-farm an illness broke out, which caused the death of 36 animals in a very short time. In necropsy all had lesions of pneumonia. From the lungs of the dead animals Bordetella bronchiseptica was isolated. The progress of the enzootic was stopped by administering Penicilline or Streptomycine injections during 3 days and Oxytetracycline in the feed during 6 days.